Development of Soft Lactation Cookies with Katuk, Moringa, and Sweet Potato: Nutritional Enhancement and Sensory Acceptability for Breastfeeding Mothers - Olivia Anggraeny; Adelya Desi Kurniawati; Clarista Aurelia Saputri; Fania Nur Aini; Helena Christiani Putri; Octaviana Anisatul; Sabila Dwi Masita Febriani (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2025)
Breastfeeding plays a crucial role in maternal and infant health, yet many mothers face challenges such as insufficient milk supply and inadequate micronutrient intake. This study aimed to develop and assess soft lactation cookies enriched with locally available galactagogues, specifically katuk leaves (Sauropus androgynus), moringa leaves (Moringa oleifera), and Cilembu sweet potatoes (Ipomoea batatas). Four cookie formulations were tested, including a control (P0) and three treatment groups (P1, P2, P3). These formulations were evaluated through nutritional analysis, physical quality tests, and sensory evaluation. The P3 formulation, containing 6.6% katuk leaves, demonstrated the highest concentrations of micronutrients, including iron (3.32 mg 100 g-1) and zinc (0.168 mg 100 g-1), and exhibited the softest texture with enhanced yellowness. Hedonic testing revealed that P3 had significantly higher taste and overall acceptability scores compared to the other formulations. This formulation provides a culturally relevant, nutrient-dense alternative for lactating mothers, addressing common micronutrient deficiencies. The results suggest that soft lactation cookies, particularly P3, may serve as an effective dietary intervention to support maternal nutrition and exclusive breastfeeding. Future studies should focus on the bioavailability and clinical impact of these cookies.